Baicalein Decreases Hydrogen Peroxide‐Induced Damage to NG108‐15 Cells via Upregulation of Nrf2. Issue 8 (August 2015) - Yeh, Chao‐Hung; Ma, Kuo‐Hsing; Liu, Pei‐Shan; Kuo, Jung‐Kuei; Chueh, Sheau‐Huei
<x xml:space="preserve">Abstract</x> Baicalein is a flavonoid inhibitor of 12‐lipoxygenase. Here, we investigated its effect on hydrogen peroxide‐induced damage to NG108–15 cells. Hydrogen peroxide activated the mitochondrial apoptotic pathway, decreased Nrf2 expression, increased reactive oxygen species (ROS) levels, reduced viability, and increased cell death after 2–24 h treatment of NG108–15 cells. Co‐treatment with hydrogen peroxide and baicalein completely suppressed the activation of mitochondrial apoptotic pathway by upregulating Nrf2 expression and reducing ROS stress and partially inhibited the effects on cell viability and cell death. Silencing of 12‐lipoxygenase had a similar protective effect to baicalein on hydrogen peroxide‐induced damage by blocking the hydrogen peroxide‐induced decrease in Nrf2 expression and increase in ROS levels. Neither protective effect was altered by addition of 12‐hydroxyeicosatetraenoic acid, the product of 12‐lipoxygenase, suggesting that hydrogen peroxide induced damage via 12‐lipoxygenase by another, as yet unknown, mechanism, rather than activating it. Co‐treatment of cells with hydrogen peroxide and N‐acetylcysteine or the Nrf2 inducer sulforaphane reduced hydrogen peroxide‐induced damage in a similar fashion to baicalein, while the Nrf2 inhibitor retinoic acid blocked the protective effect of baicalein. Silencing Nrf2 also inhibited the protective effects of baicalein, sulforaphane, and N‐acetylcysteine and resulted in high ROS levels, suggesting ROS elimination was mediated by Nrf2. Taken together our results suggest that baicalein protects cells from hydrogen peroxide‐induced activation of the mitochondrial apoptotic pathway by upregulating Nrf2 and inhibiting 12‐lipoxygenase to block the increase in ROS levels. Hydrogen peroxide also activates a second mitochondrial dysfunction independent death pathway which is resistant to baicalein. J. Cell. Physiol. 230: 1840–1851, 2015. © 2015 Wiley Periodicals, Inc.